Multidisciplinary approach in a case of hemifacial microsomia: Speech and language pathologist contributions. - Peris Hernandez, Cristina; Rosell Clarí, Vicent (Revista de Investigación en Logopedia, 2019)
This study shows the initial pathology, the evolution and the treatment of a clinical case of Hemifacial Microsomia from childhood to adolescence, placing special emphasis on the approach of the case from the point of view of Speech and language pathology. The objective of this research was to show the performances of the speech pathologist at the level of evaluation and rehabilitation of the functional alterations involved: respiration, chewing and speech. The methodology used was that of the case study, for which purpose it was decided to chronologically present the instruments and measures used, as well as the interventions carried out in three phases: from 0 to 4 years, from 5 to 11 and from 12 to 16 years. The results show the favorable evolution of the patient in the acquisition and mainte-nance of a pattern of nasal breathing, which includes the correct placement of the tongue at rest, the acquisition of a pattern of alternating bilateral chewing and a remarkable improvement in the quantity and quality of masticatory cycles, as well as the normalization of labial competence and the elimination of noises during swallowing. On the other hand, in the rehabilitative treatment performed after the arthroplasty, positive results were also recorded in the range of mandibular movement at the vertical and lateral levels, restoring retrusion. Therefore, we concluded that speech and language intervention was beneficial both in the rehabilitation of the functions and in the aesthetic changes at the level of the orofacial structure